Efficacy of a feed additive consisting of ferrous lysinate sulfate for all animal species (Phytobiotis Futterzusatzstoffe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the efficacy of ferrous lysinate sulfate (Plexomin® L‐Fe) for all animal species. The additive has not been previously authorised as a feed additive in the European Union (EU). The safety of the additive for the target species, consumer, user and the environment has already been assessed in previous opinions. However, the efficacy remained inconclusive due to the absence of evidence of the bioavailability of the iron contained in the additive in the trials submitted either with chickens for fattening or with weaned piglets. For the present assessment, the applicant submitted a recalculation of the previous data on weaned piglets, which did not show evidence of bioavailability. Therefore, in the absence of adequate data, the FEEDAP Panel could not conclude on the efficacy of ferrous lysinate sulfate for all animal species.